1997
DOI: 10.1007/s002040050403
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450-dependent drug oxidation activities in liver microsomes of various animal species including rats, guinea pigs, dogs, monkeys, and humans

Abstract: Levels of cytochrome P450 (P450 or CYP) proteins immunoreactive to antibodies raised against human CYP1A2, 2A6, 2C9, 2E1, and 3A4, monkey CYP2B17, and rat CYP2D1 were determined in liver microsomes of rats, guinea pigs, dogs, monkeys, and humans. We also examined several drug oxidation activities catalyzed by liver microsomes of these animal species using eleven P450 substrates such as phenacetin, coumarin, pentoxyresorufin, phenytoin, S-mephenytoin, bufuralol, aniline, benzphetamine, ethylmorphine, erythromyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
93
2
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(103 citation statements)
references
References 34 publications
6
93
2
2
Order By: Relevance
“…Therefore, species differences in CYP activities, which have been reported in a number of studies, need to be clarified between experimental animals and humans. Humans and rodents, such as mice and rats, generally exhibit greater species differences in CYP activities; however, rodents have frequently been used as animal models in drug discovery [4][5][6][7][8][9][10][11]. On the other hand, Bogaards et al [12] reported that CYP1A activity in mouse microsomes and CYP3A activity in mouse and rat microsomes were similar to those in human microsomes [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, species differences in CYP activities, which have been reported in a number of studies, need to be clarified between experimental animals and humans. Humans and rodents, such as mice and rats, generally exhibit greater species differences in CYP activities; however, rodents have frequently been used as animal models in drug discovery [4][5][6][7][8][9][10][11]. On the other hand, Bogaards et al [12] reported that CYP1A activity in mouse microsomes and CYP3A activity in mouse and rat microsomes were similar to those in human microsomes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although dogs are frequently used as non-rodent species in nonclinical studies, information concerning the canine CYP system is more limited. The hepatic metabolism of specific human CYP2C substrates, such as tolbutamide, warfarin, and (S)-mephenytoin, is known to be impaired more in dogs than in humans [13], whereas metabolism studies using liver microsomes demonstrated that the metabolism of human CYP2D substrates, such as bufuralol and dextromethorphan, was similar in humans and dogs [10,11,14]. Monkeys were originally considered to have pharmacokinetic properties similar to those of humans due to genetic similarities, however, previous studies showed that the bioavailability (BA) of some drugs including human CYP3A substrates was markedly lower in monkeys than in humans [7,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of CYP450 enzyme per mg of liver protein is similar in dogs and humans, but less than that of rats, monkeys, and guinea pigs (59). The overall content of CYP450 in the liver, however, is not predictive of a species' ability to metabolize any single compound.…”
Section: Hepatic Metabolismmentioning
confidence: 87%
“…Comparisons of the sequence of canine isoforms with homologues of other species have shown a high degree of amino acid sequence identity, (6) but the similarities in sequence have not always predicted similarities in enzymatic characteristics. In an effort to better understand the metabolic profile of the canine CYP450s, numerous studies have been conducted comparing the activity and specificity of dog CYP450 isozymes with those of other species (6,8,56,59). An overarching conclusion in many of these studies is that there are significant differences in the metabolic activities of dog CYP450s when compared with other species.…”
Section: Hepatic Metabolismmentioning
confidence: 99%
See 1 more Smart Citation